Peningkatan Kualitas Laporan Keuangan UMKM Toko Sembako Dan Laundry Care - Ali Muddin Ritonga; Yudas Tadius Andi Candra (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
In order to maintain business continuity and growth, Micro, Small and Medium Enterprises (MSMEs) need assistance in preparing financial reports. The importance of assistance in preparing financial reports for Micro, Small and Medium Enterprises (MSMEs), especially for Toko Laras Barokah and Laundry Care is included in this activity. Accurate and timely financial reports are very important for MSMEs to run and develop their companies. This research uses a qualitative methodology by providing direct support to the two MSMEs in preparing their financial reports. The aim of this coaching activity is to perfect the accounting procedures of MSME owners and increase their awareness of the importance of financial reports. The findings of this research show how good mentoring can improve the quality of MSME financial reports, which will facilitate better business decision making and increase access to funding and other resources.